ANALISIS BUDAYA HUKUM DAN DIMENSI HUKUM JAKSA DAN ADVOKAD - PUTRA HALOMOAN (IAIN Padangsidimpuan, 2017)
This article is about an analysis of cultural law in dimension for legal profession about the prosecutor and advocacy. The dimension of law in a prosecutor in accordance with applicable regulations. Indonesian Prosecutors Institution is Government Institution which is implementing the state power in the field of prosecutions and authorizes another based on undang-undang, it has the authorities in law enforcement and justice. Referring to Undang-undang number 16 on the year 2004 about the Indonesian prosecutors' institution, it is as one law enforcement agencies that are required to have a greater role in enforcing the rule of law, protection of general interest, upholding human rights, and eradicating corruption, collusion, and nepotism. Then, an Advocate is free, independent, and responsible profession in enforcing a law, so it should be guaranteed and protected by the state through Undang-undang by the implementation of maintaining the supremacy of justice. An Indonesian advocate must be able to aware of the need to give and legal aid for those who need it in non-discrimination without seeing the differences of religion, trust, tribes, political beliefs, and social position